Preliminary Studies on the Effect of a Permanent Cover Crop and Root Pruning on an Irrigated Colombar Vineyard - Saayman, D.; Van Huyssteen, L. (South African Journal of Enology and Viticulture, 2017)
An experiment was conducted in the Olifantsrivier irrigation area to assess the effect of different cultivation treatments, such as clean cultivation, a permanent cover crop and of root pruning by means of deep ripping, on the growth and yield of a flood irrigated, ungrafted Colombar vineyard. The best vine performance was obtained with clean cultivation. Although a cover crop plus deep cultivation improved water infiltration, competition of the permanent cover crop seriously suppressed vine growth and yield, and also caused a notable decrease in the nitrogen status of the vines. There were indications that severe root pruning by means of deep ripping increased the negative effect of the permanent cover crop on vine performance. Clean cultivation remains an effective way of weed control provided there is no soil compaction hazard and it is economically feasible.